Molecular mechanisms of how black barley accumulates higher anthocyanins than blue barley following transcriptomic evaluation and expression analysis of key genes in anthocyanins biosynthesis pathway - Hasan, Md. Mahmudul; Mia, Md. Sohel; Yang, Jiazhen; Zeng, Yawen; Yang, Tao (Frontiers in Plant Science, 2025)
Barley is not only a major food crop but also a medicinal plant which has considerable quantities of flavonoids. Among all flavonoids, anthocyanins play a crucial role in pigmentation, pollination, seed dispersal in plants. Anthocyanins also have antioxidant properties. Varietal differences significantly affect anthocyanins content in barley. Therefore, anthocyanins content are significantly higher in black barley than the blue one. To explore the molecular mechanisms of higher anthocyanins content in black barley, transcriptomic analysis was done to elucidate the involvement and expression of new genes in anthocyanins biosynthesis in two barley. In transcriptomic analyses, 10,579 new genes were identified, and 5,912 were functionally annotated. Twelve types of alternative splicing were found in 10,579 unigenes. Among 7,113 differentially expressed genes (DEGs), 3,235 were significantly up-regulated. The existence of the significant protein-protein interaction and involvement of many DEGs in various biological, cellular and molecular processes might reveal their significant influence on plant growth, development, yield and anthocyanins biosynthesis. Involvement of DEGs in phenylpropanoid and flavonoids biosynthesis in the black barley might be due to their great involvement in flavonoid biosynthesis, including anthocyanins. Higher expression of ANS1, LDOX1, LDOX2, and LDOX3 genes of anthocyanins biosynthesis pathway in black barley than the blue one might reveal their great involvement in biosynthesis, accumulation and transformation of anthocyanins into the seed of black barley. Therefore, the current first report on DEGs in two types of barley, their expression, the unigenes and expression of major genes in anthocyanins biosynthesis pathway might guide plant biologists in reprogramming the anthocyanins biosynthesis pathway to develop barley with improved anthocyanins content by developing and transforming synthetic genetic circuits into black barley.